2020
DOI: 10.1177/1550059419896723
|View full text |Cite
|
Sign up to set email alerts
|

Altered P3a Modulations to Emotional Faces in Male Patients With Chronic Schizophrenia

Abstract: Existing evidence suggests that patients with schizophrenia may have a deficit in processing facial expressions. However, the neural basis of this processing deficit remains unclear. A total of 20 men diagnosed with chronic schizophrenia and 13 age- and sex-matched controls participated in the study. We investigated visual N170 and P3a components evoked in response to fearful, happy, and sad faces during an emotion discrimination task. Compared with control subjects, patients showed significantly smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…As previously described, the P300 component could reflect the allocation of attentional resources. [ 36 ] In the present study, the mean P300 amplitudes significantly decreased among all three facial expressions (happy, fearful, and neutral) in SZs, and this finding is consistent with that of previous research,[ 5 , 18 , 37 ] indicating that SZs may have a deficit in attentional resources. Moreover, compared with neutral or positive stimuli (neutral or happy faces), negative stimuli could trigger larger P300 amplitudes in HCs, while there was no significant difference among stimulus types in SZs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As previously described, the P300 component could reflect the allocation of attentional resources. [ 36 ] In the present study, the mean P300 amplitudes significantly decreased among all three facial expressions (happy, fearful, and neutral) in SZs, and this finding is consistent with that of previous research,[ 5 , 18 , 37 ] indicating that SZs may have a deficit in attentional resources. Moreover, compared with neutral or positive stimuli (neutral or happy faces), negative stimuli could trigger larger P300 amplitudes in HCs, while there was no significant difference among stimulus types in SZs.…”
Section: Discussionsupporting
confidence: 93%
“…[ 5 ] The results are mixed regarding specific emotional faces, such as fear, neural, happiness, etc., A recent study has revealed that fearful and happy faces triggered smaller P3a amplitude in SZs than HCs. [ 18 ] Others reported that negative faces could trigger a greater P300 amplitude in HCs, whereas a smaller P300 amplitude was observed in SZs compared with positive faces. [ 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…The visually evoked N170 component is a negative potential recorded using electroencephalography (EEG) at occipitotemporal electrodes at around 170 ms after stimulus onset and reflects the early phase of face processing ( 8 ). A face-sensitive N170 reduction has been repeatedly reported in patients with SZ ( 9 11 ). Moreover, it has been suggested that this reduction in the face-sensitive N170 is significantly associated with social dysfunction in patients with SZ ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 84%
“…Reductions in P3a amplitude have been shown in individuals with chronic SZ ( 64 , 67 ), after their first episode of psychosis ( 68 70 ) as well as in individuals classified as being high risk for developing SZ ( 71 73 ). This evidence suggests that P3a could serve as an important marker of SZ, including for those at risk of developing SZ.…”
Section: Introductionmentioning
confidence: 99%